Author Correction: Traps and transport resistance are the next frontiers for stable non-fullerene acceptor solar cells (Nature Communications, (2022), 13, 1, (3786), 10.1038/s41467-022-31326-z) - Wöpke, Christopher; Göhler, Clemens; Saladina, Maria; Du, Xiaoyan; Nian, Li; Greve, Christopher; Zhu, Chenhui; Yallum, Kaila M.; Hofstetter, Yvonne J.; Becker-Koch, David; Li, Ning; Heumüller, Thomas; et al. (Nature Communications, 2022)
The original version of this Article contained an error in Fig. 2, in which three data sets (represented by circles, squares and triangles, respectively)were shifted along the x-axis by one data point, leadin g to an incorrect representation of the “Exp. suns-Voc” data (the symbols) in Fig. 2a and 2b. The correct version of Fig. 2 is:(Figure Presented.).This has been corrected in both the PDF andHTMLversions of the Article.
CRIS-Team Scopus Importer:2022-08-12

Traps and transport resistance are the next frontiers for stable non-fullerene acceptor solar cells - Woepke, Christopher; Goehler, Clemens; Saladina, Maria; Du, Xiaoyan; Nian, Li; Greve, Christopher; Zhu, Chenhui; Yallum, Kaila M.; Hofstetter, Yvonne J.; Becker-Koch, David; Li, Ning; Heumüller, Thomas; et al. (Nature Communications, 2022)
Stability is one of the most important challenges facing material research for organic solar cells (OSC) on their path to further commercialization. In the high-performance material system PM6:Y6 studied here, we investigate degradation mechanisms of inverted photovoltaic devices. We have identified two distinct degradation pathways: one requires the presence of both illumination and oxygen and features a short-circuit current reduction, the other one is induced thermally and marked by severe losses of open-circuit voltage and fill factor. We focus our investigation on the thermally accelerated degradation. Our findings show that bulk material properties and interfaces remain remarkably stable, however, aging-induced defect state formation in the active layer remains the primary cause of thermal degradation. The increased trap density leads to higher non-radiative recombination, which limits the open-circuit voltage and lowers the charge carrier mobility in the photoactive layer. Furthermore, we find the trap-induced transport resistance to be the major reason for the drop in fill factor. Our results suggest that device lifetimes could be significantly increased by marginally suppressing trap formation, leading to a bright future for OSC.
CRIS-Team Scopus Importer:2022-07-15